Optimization of a four junction solar cell CPV system using ray tracing and SPICE modeling - Sharma, Pratibha; Wilkins, Matthew; Schriemer, Henry; Hinzer, Karin (Université d'Ottawa | University of Ottawa, 2015)
Concentrating optics generally produce spatially and spectrally non-uniform optical profiles across the multijunction solar cells (MJSC) typically used in concentrator photovoltaic (CPV) systems, degrading fill factors and thereby reducing module efficiencies. These effects may be more pronounced if the primary-to-receiver working distance is sub-optimal and if the system does not track the sun accurately. We integrate ray tracing with a distributed equivalent circuit model to simulate the performance of a four-junction solar cell under a Fresnel-lens-based CPV system of 1250X geometric concentration. The impacts on system efficiency of varying both the primary-to-receiver working distance as well as the tracking accuracy are evaluated. Our results indicate a relative enhancement of 6.67% when we optimize the working distance based on an integrated systems approach using the full optical distribution as an input to a 2-D distributed equivalent circuit model of the MJSC, as opposed to a uniform profile 1-D treatment. With a more optimized system, we find a relative reduction in efficiency of 10.7% for a tracking error of 1º, with the penalty for improper tracking increasing for sub-optimal primary-to-receiver working distances.